Does Digital Waqf Intention Lead to Actual Use? Evidence from West Java - Auni Alifah Sukirman; Indri Yuliafitri; Nabela Hapsari (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
Digital waqf has emerged as a transformative innovation in Islamic philanthropy, linking traditional endowment practices with contemporary digital technology; however, despite Indonesia’s estimated annual cash waqf potential of IDR 180 trillion, less than 2% has been realized due to limited public literacy and participation. This study aims to examine the determinants of digital waqf adoption by applying the Technology Acceptance Model (TAM), with particular attention to perceived usefulness, perceived ease of use, and waqf literacy in shaping behavioral intention and actual use. Data were collected from 271 Muslim respondents in West Java and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that perceived ease of use significantly influences both perceived usefulness and behavioral intention, while waqf literacy also positively affects intention. In contrast, perceived usefulness does not show a significant effect on behavioral intention, suggesting that ease, understanding, and cognitive-religious awareness play a more prominent role than functional benefits in encouraging participation. Behavioral intention is confirmed as a strong predictor of actual use, highlighting its role as a critical link between awareness and real engagement in digital waqf activities. These results extend the TAM framework by incorporating waqf literacy as a cognitive-religious factor relevant to philanthropic technology adoption. Practically, the study suggests that waqf institutions should prioritize user-friendly platform design, expand literacy initiatives, and strengthen trust through transparency and accessibility to convert intention into sustained participation. ABSTRAK - Apakah Niat Berwakaf Digital Mempengaruhi Penggunaan Aktual? Bukti dari Jawa Barat. Wakaf digital hadir sebagai inovasi penting dalam filantropi Islam yang menghubungkan praktik wakaf tradisional dengan teknologi digital modern. Namun demikian, dari potensi wakaf uang nasional yang diperkirakan mencapai Rp180 triliun per tahun, realisasinya masih di bawah 2% akibat rendahnya literasi dan partisipasi masyarakat. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang memengaruhi adopsi wakaf digital dengan menggunakan kerangka Technology Acceptance Model (TAM), khususnya persepsi kemanfaatan, persepsi kemudahan penggunaan, dan literasi wakaf dalam membentuk niat berperilaku serta penggunaan aktual. Data diperoleh dari 271 responden Muslim di Jawa Barat dan dianalisis menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM). Hasil penelitian menunjukkan bahwa kemudahan penggunaan berpengaruh signifikan terhadap persepsi kemanfaatan dan niat berperilaku, sementara literasi wakaf juga memberikan pengaruh positif terhadap niat. Sebaliknya, persepsi kemanfaatan tidak berpengaruh signifikan terhadap niat, yang mengindikasikan bahwa faktor kemudahan, pemahaman, dan kesadaran kognitif-religius lebih dominan dibandingkan manfaat fungsional dalam mendorong partisipasi. Niat berperilaku terbukti sebagai prediktor utama penggunaan aktual, yang menegaskan perannya sebagai penghubung antara kesadaran dan tindakan nyata dalam wakaf digital. Temuan ini memperluas TAM dengan memasukkan literasi wakaf sebagai dimensi kognitif-religius yang relevan dalam adopsi teknologi filantropi. Secara praktis, lembaga wakaf perlu mengutamakan desain platform yang mudah digunakan, memperluas program literasi, serta meningkatkan kepercayaan melalui transparansi dan aksesibilitas guna mendorong partisipasi berkelanjutan.